Greener terpene-terpene eutectic mixtures as hydrophobic solvents - Martins, Mónia A.R. (2018)
Natural products can be the basis for the development of green solvents, relevant for the advancement of new, more sustainable processes and products. In this work, 10 binary mixtures constituted by terpenes are prepared and characterized. Their solid−liquid phase diagrams show that room-temperature solvents can be prepared from solid terpenes in a wide composition range. These diagrams are accurately described by the conductor-like screening model for real solvents, showing it to be a useful predictive tool for the design of novel natural solvents. At the eutectic point, these mixtures possess low viscosities, densities lower than water, and high boiling temperatures. The low water solubility in the eutectic solvents together with its negligible impact on the properties measured is a strong indicator of the hydrophobic character of these mixtures. The tunable character of these mixtures is demonstrated by studying the solvatochromic parameters in the entire concentration region, the properties of the final solvents being tuned by simply varying the mole fraction of the terpenes. The high potential of this tunable character is shown in the selective extraction of dyes from their aqueous solutions. This work is expected to devise new insights concerning these solvents as well as to boost their application in green industrial processes.